Confirmatory Factor Analysis of Social and Emotional Learning of Secondary Student in Office of the Basic Education Commission - Inta, Montri (Life Sciences and Environment Journal, 2016)
The purpose of this research were 1) to confirmatory factor analysis of social and emotional learning of secondary student 2) to consistent test of the social and emotional learning model of secondary student. The sample this research consisted of 1,344 Secondary Student attending the academic in the first semester of 2016 at 18 schools under the office of the basic education commission in Northern provinces consisted Chiang Mai, Lumphun, and Chiang Rai. They were obtained using the Multi – Stage Random Sampling technique. Questionnaire was Likert scale 5 level, with 92 items. The reliability of whole scale was = 0.948 confirmatory factor analysis and consistent test of the social and emotional learning model of secondary student by using Mplus 6.12 The results revealed that 1) the confirmatory factor analysis of social and emotional learning of secondary student consisted 5 factors according to priority of factor loading as following: Self-awareness (0.782), Self-management (0.906), Responsible decision making (0.953), Relationship skills (0.971) and Social- awareness (0.986). 2) The consistent test of the social and emotional learning model of secondary student found that the construct validity of scale and the model fitted well and the empirical data. The goodness of fit measures for the model were (c2= 76.547, df = 60, p-value = 0.073, RMSEA=0.014, CFI=0.999, TLI = 0.997, SRMR=0.011) and were statistical significant at level of 0.01.